2022
DOI: 10.1093/molbev/msab367
|View full text |Cite
|
Sign up to set email alerts
|

Synergism, Bifunctionality, and the Evolution of a Gradual Sensory Trade-off in Hummingbird Taste Receptors

Abstract: Sensory receptor evolution can imply trade-offs between ligands, but the extent to which such trade-offs occur and the underlying processes shaping their evolution is not well understood. For example, hummingbirds have re-purposed their ancestral savory receptor (T1R1-T1R3) to detect sugars, but the impact of this sensory shift on amino acid perception is unclear. Here, we use functional and behavioral approaches to show that the hummingbird T1R1-T1R3 acts as a bifunctional receptor responsive to both sugars a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The sensitivity of T1R1-T1R3 to amino acids and sugars changes across different bird species. Alanine, lysine, arginine, asparagine, valine, serine, and glycine trigger the T1R1-T1R3 heterodimer more than other amino acids (Cockburn et al, 2022).…”
Section: Umami Tastementioning
confidence: 96%
See 2 more Smart Citations
“…The sensitivity of T1R1-T1R3 to amino acids and sugars changes across different bird species. Alanine, lysine, arginine, asparagine, valine, serine, and glycine trigger the T1R1-T1R3 heterodimer more than other amino acids (Cockburn et al, 2022).…”
Section: Umami Tastementioning
confidence: 96%
“…Rajapaksha et al (2016) reported 767 taste buds in chicken, 66% of which on the palate and the rest on the base of the oral cavity. In the past few years, fascinating aspects of the avian taste system have been discovered which highlight the evolutionary relevance of the avian taste system to adapt to dietary requirements in several bird species (Baldwin et al, 2014;Toda et al, 2021;Cockburn et al, 2022). Looking to the future, the recent release of the whole genome sequence of 363 bird species in 2020 and the initiative to sequence the genome of all the 10,000 bird species (B10K project: https://b10k.genomics.cn) will provide the opportunity to further understand the role of taste system in avian biology and evolution (Feng et al, 2020).…”
Section: A Brief Historical Perspective On the Discovery Of The Avian...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although in general five basic taste modalities act in concert to assess the nutritional quality of food, a considerable number of animals have lost some taste modalities ( Antinucci and Risso, 2017 ). A well known example is the pseudogenization of the sweet taste receptor in all bird species, although several bird clades with a high demand for sweet tasting nutritional resources such as nectar, achieved the subsequent modification of the umami taste receptor for sweet compound detection ( Baldwin et al, 2014 ; Toda et al, 2021 ; Cockburn et al, 2022 ). In the past, it was believed that birds possess an inferior sense of taste, an assumption that was supported by the loss of the sweet tasting ability as well as a small number of bitter taste receptors ( Niknafs and Roura, 2018 ).…”
Section: Introductionmentioning
confidence: 99%